TRANSFORMASI GARAP LADRANG PANGKUR KE DALAM MUSIK KRUMPYUNG DI KABUPATEN PURBALINGGA - Galang Pangestu; Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
This research aims to reveal the process and factors that influence the transformation of Ladrang Pangkur into Krumpyung music by Paguyuban Sri Rahayu Tresna Sejati in Purbalingga Regency. The problem is studied using the theory proposed by Suradi related to transformation, and the concept of garap by Rahayu Supanggah. The method used in this research is qualitative research method. The initial stage is data collection by observation, interview, and documentation. The second stage is data analysis using data reduction, data presentation and conclusion drawing techniques. The next stage is data verification before presenting the data. The result of transforming Ladrang Pangkur into Krumpyung Music shows imitation, which can be seen through the technique, pattern, rhythm, laras, and pathet of Javanese gamelan. In addition, the players also create new techniques and patterns in Krumpyung Music.